(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
The goal of this article is to identify and share the best practices and innovations to enable teaching and learning to take place during times of VUCA (Volatile, Uncertain, Complex, and Ambiguous) such as the coronavirus pandemic. This will help lay the foundations for more inclusive and equitable approaches to education when the crisis subsides. The main response to school closures is to dive headlong into academic cyberspace and remote learning, creating a human-machine symbiosis. Ideally, specific contents, learning outcomes, and a set of instructions are desirable. Different media and technologies can be used to assist students to learn in different ways and achieve different outcomes, thus also individualizing learning more. Technologies can be compared along several characteristics. These characteristics form a basis for analyzing new technologies, to see where they fit within the existing environment, and to evaluate their potential benefits and limitations. Nowadays, technologies have a tendency to become more ‘communicative’ and ‘media rich’, thus offering educators and students powerful tools to attain desired learning outcomes.